The best man holiday [videorecording (DVD)] - Lee, Malcolm D., 1970-; Diggs, Taye; Long, Nia; Chestnut, Morris; Howard, Terrence; Lathan, Sanaa; Hall, Regina (2014)
At a fifteen year reunion over the Christmas holidays, a group of college friends soon discover how simple it is for old rivalries and romances to resurface.